Awareness toward the code of ethics among nursing students - Kang, Se-Won (Advances in Social Sciences Research Journal, 2019)
This descriptive study aimed to investigate the change in awareness toward the code of ethics for nurses among nursing students. The participants were 61 nursing students at a university in P City, South Korea. Data collection was conducted in September 2017 and March 2019. Statistical analysis was performed using mean, standard deviation, percentage, and paired samples t-test. Nursing students’ awareness toward the code of ethics for nurses significantly improved by program year level (t = 3.284, p = 0.001), with fourth-year scores outperforming their second-year scores in the following: “nurse and nursing clients” (t = 3.163, p = 0.002), “obligation of nurse as experts” (t = 3.268, p = 0.002), and “nurse and cooperators” (t = 3.251, p = 0.002). It is necessary to develop a variety of ethical education methods that use ethical codes to equip nursing students with professional ethics and morality.